2022
DOI: 10.1038/s41598-022-08392-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic determinants of hearing outcomes in children with congenital cytomegalovirus infection

Abstract: Congenital cytomegalovirus (cCMV) infection is the most prevalent cause of non-genetic sensorineural hearing loss (SNHL) in children. However, the prognostic determinants of SNHL remain unclear. Children with cCMV infection in a tertiary hospital were enrolled. The presence of cCMV-related symptoms at birth, the newborn hearing screening (NHS) results, and the blood viral loads were ascertained. Audiologic outcomes and initial blood viral loads were compared between different groups. Of the 39 children enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Several researchers expressed the need to further establish the predictive role of viral load (33,34,51). Our results showed that viral load is not associated with clinical, neurological or laboratory findings at birth.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Several researchers expressed the need to further establish the predictive role of viral load (33,34,51). Our results showed that viral load is not associated with clinical, neurological or laboratory findings at birth.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, significantly higher mean or median values of blood viral load in newborns with symptomatic cCMV infection compared with those with asymptomatic infection have been described . In addition, some studies have reported that newborns with congenital hearing loss had an equal or higher initial viral load compared with newborns with normal hearing at birth. The contradictory results of these different studies might be explained by the low sample size, different definitions, inclusion criteria, or outcome measurements.…”
Section: Discussionmentioning
confidence: 95%
“…However, the small cohort size limits the significance of the findings. In two different cohorts of cCMV from Taiwan, identified by a combination of newborn screening and screening of symptomatic infants, symptomatic infection, high CMV viral load at birth and failed newborn hearing screening were identified as prognostic indicators for SNHL in the newborn period [43 ▪ ] whereas low birth weight, gestational age and prolonged viral shedding correlated with late-onset SNHL [44]. None of these risk-factors predicted vestibular dysfunction.…”
Section: Managementmentioning
confidence: 98%
“…Infants with SNHL need hearing screening at frequent intervals as SNHL is the most common sequelae of cCMV and 40% of SNHLs are late onset, i.e., after one month of age. The Incidence of SNHL is 25% to 65 % in symptomatic and 6% to 25% in asymptomatic infants [11]. Other permanent sequelae, including microcephaly, motor deficits, and chorioretinitis, have also been reported in infants with asymptomatic cCMV [12].…”
Section: Discussionmentioning
confidence: 99%